Transcriptomic sequencing and expression verification of identified genes modulating the alkali stress tolerance and endogenous photosynthetic activities of industrial hemp plant - Zeyu Jiang; Di Wang; Ye Che; Sikandar Amanullah; Ling Zhang; Siyuan Jie; Wei Yang; Mingze Wang; Lina Wang; Guochao Qi (PLoS ONE, 2025)
Hemp (Cannabis sativa L.) has a long cultivation history around the world. In northeast part of China, the alkaline soil geology severely reduces crop production. In this study, we tried to evaluate the impacts of alkali-induced stress on the photosynthetic status and physiological indices of hemp plants. The microscopic evaluation of endogenous ultrastructure clearly demonstrated significant oxidative damage to the structure of the photosynthetic tissues associated with the membrane, resulting from an increase in the levels of MGDG and DGDG. The deformed photosynthetic apparatus induced by alkali-stress significantly inhibited the biosynthesis process of photosynthetic pigments, causing 49.25%, 52.72%, 65.31%, and 28.13% loss in total Chl, Chl a, Chl b, and carotenoids, respectively. Meanwhile, the reduction in chlorophyll fluorescence parameters (Pn (74.62%), Gs (39.69%), and Tr (83.77%)) along with the obviously increased MDA (28.57%) and H2O2 (35.18%) content exhibited that the inhibitory effect of alkali-stress not only decreased the photosynthetic efficiency by intercepting the nutrient supply but also generated excessive ROS, resulting in oxidative stress. Transcriptomic analysis (RNA-sequencing) revealed the considerably enriched GO terms as well as KEGG pathways that exposed the significant DEGs. The qPCR expression evaluation of down-regulated chlorophyll biosynthesis-related major genes (GOGAT (LOC115699366) and HEMA (LOC133032634)) and photosystem-related major genes (PSB (LOC115701338) and HCF (LOC115707994)) exhibited important molecular evidence for modulating the photosynthesis activity of hemp plant under devastating mechanism of alkali-stress. However, the transcript patterns of photorespiration-related genes (GOX (LOC115697365) and GDC (LOC115707082)) showed a slower decreasing trend at late stress stage (at 24 ~ 48 h), and the transcription of SGAT gene (LOC115699360) was even enhanced by stress treatment at 48 h, probably in an attempt to adjust cellular carbon balance and elevate the antioxidant properties induced by alkali-stress.